Effects of external wall composition on embodied CO2 emission and economic cost in hot summer and cold winter zone of China - Jiang Lu; Jiantao Weng (Lowland Technology International, 2020)
External walls make up the main components of the building envelope. Numerous standards were proposed addressing the thermal performance, whereas the embodied CO2 emission and economic cost of different external walls lacks further study. Four typical types of external walls, i.e., external insulation (Wall 1), internal insulation (Wall 2), self-insulation (Wall 3), and combined internal and external insulation (Wall 4), are designed. The thermal performance of Walls 1–4 is set to be the same by adjusting the thickness of insulation. The four walls are considered to be part of a typical residential building located in Hangzhou, China. The embodied CO2 emissions and economic costs of Walls 1–4 are quantitatively compared based on life cycle assessment and life cycle cost. Wall 3 performs optimally on both reducing embodied CO2 emission and reducing economic costs. Although Wall 4 does not have an obvious advantage on reducing embodied CO2 emissions, the total economic cost of Wall 4 is 14.9% and 9.5% lower than that of Wall 1 and Wall 2 respectively, which indicates its potential in possessing a certain amount of the market share. This study provides helpful data and evaluating procedures for establishing standards in future carbon reduction of buildings.